Beyond seeing and listening: children born from conflict-related sexual violence - Távara, Gabriela (International journal of transitional justice, 2024)
This essay discusses some points made by the three books under review regarding how children born of conflict-related sexual violence have not been seen and listened to by those working in the field of transitional justice. To this end, it explores some of the reasons behind this oversight, including generalized assumptions about their relationships with their mothers, families and communities. It also discusses some of the limitations of the current transitional justice framework to address the plight of these children. Finally, the essay emphasizes the importance of analyzing more deeply the particular context in which these children are embedded. To this end it draws from some of the frameworks presented in the three books under review, which allow for a more capacious comprehension of the situation of children born of conflict-related sexual violence.